Differentiation of COVID-19 Pneumonitis and ICI Induced Pneumonitis - Dumoulin, Daphne W.; Gietema, Hester A.; Paats, Marthe S.; Hendriks, Lizza E. L.; Cornelissen, Robin (Frontiers in Oncology, 2020)
Immune checkpoint inhibitors (ICI) have become standard of care treatment for several tumor types and stages. An important complication of ICI is ICI-induced pneumonitis. Cancer has been reported to be one of the risk factors for serious severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pneumonia, that has engulfed the world in the last couple of months. In cancer patients treated with ICI presenting at the emergency department during the COVID-19 pandemic, correct diagnosis can be challenging. Symptoms and radiological features of ICI pneumonitis can be overlapping with those of COVID-19 pneumonia. For the latter, no proven therapy exists, although multiple therapies are under investigation. In contrast, ICI pneumonitis must be treated in most cases with immunosuppressive therapy, as this is a potentially fatal adverse event. It has been suggested that immunosuppression increases the risk of complicated COVID-19. Therefore, distinction between these two entities is warranted. This paper will summarize the clinical, radiological features as well as additional investigations of both entities, leading to a suggested diagnostic algorithm. This algorithm may be a supportive tool for clinicians to diagnose the underlying cause of the pneumonitis in patients treated with ICI during this COVID-pandemic.